PERANCANGAN FILM FEATURE TEPAK SIRIH PALEMBANG - Satria Nugraha; Mukhsin Patriansyah; Hardono Wisnu Wijaya (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Cultural assets in the form of Tepak sirih Palembang is one of the nation's identity should be maintained existence, because Tepak sirih has historical and philosophical significance that is very interesting to know. But now the existence of tepak sirih already begun eliminated by more modern decorative objects more attractive. One way to maintain, inform and develop is through the medium of visual communication in the form of films. Feature films chosen for this film can inform the facts according to the director wishes to show a more interesting storyline. Through a feature film Tepak sirih Palembang expected the public will become more aware of and interested in the cultural assets of the town of Palembang, moreover, the hope is that people and governments can participate preserve and develop the cultural assets typical of Palembang through various media. Make a distinctive cultural assets Palembang remain, grow and be able to compete with the craft from abroad or modern. Cultural assets of the nation is in need of attention from the public, especially the younger generation, to arts and crafts typical of Indonesia could always be this nation's identity. National identity is indispensable in today's modern era of globalization, to maintain the values of noble traditions of Indonesia that has existed since time immemorial.